GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 776 species occurrences available in GBIF matching the query: TaxonKey: Tanaidae Dana, 1849 HasCoordinate: true HasGeospatialIssue: false. The dataset includes 776 records from 56 constituent datasets: 1 records from MNA (Section of Genoa) and NIWA Invertebrate Collection - Ross Sea Tanaidacea. 34 records from Marine Biological Association - Marine survey data (Professional) held by MarLIN. . 5 records from The SERTC Invertebrate Database: Invertebrates of the southeastern United States. 1 records from Colección de Crustacea del Museo Nacional de Historia Natural de Chile. 5 records from Marine Biological Association - DASSH Data Archive Centre Academic surveys. 2 records from COMARGIS: Information System on Continental Margin Ecosystems. 1 records from Geographically tagged INSDC sequences. 1 records from (Table B) Abundance of benthic fauna associated with shrimp swarms at hydrothermal fields on the Mid-Atlantic Ridge. 19 records from Bases de datos de Tanaidaceos (Crustacea: Peracarida) del Mar Caribe mexicano. 12 records from Natural Geography In Shore Areas (NaGISA) Dataset. 11 records from Countryside Council for Wales - Pembrokeshire Marine Species Atlas. 8 records from A Biological Survey of the Waters of Woods Hole and Vacinity. 5 records from Bishop Museum Data (OBIS distribution) (USOBIS). 19 records from SINBIOTA - marine data (OBIS South America, BRAZIL). 1 records from Gesamtartenliste Bremerhaven, Helgoland und Sylt. 26 records from CAS Invertebrate Zoology (IZ). 3 records from Senckenberg - CeDAMar Resource. 1 records from NODC WOD01 Plankton Database. 1 records from Artenvielfalt der Nordsee - Helgoland. 4 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 46 records from NBI. 5 records from Bernice P. Bishop Museum. 64 records from Joint Nature Conservation Committee - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by JNCC. 3 records from (Table A) Abundance of species detected in mussel beds within hydrothermal fields on the Mid-Atlantic Ridge. 7 records from Albany Museum Grant. 3 records from Gwaii Haanas Invertebrates (OBIS Canada). 2 records from Collection Crustacea - ZMB. 7 records from Countryside Council for Wales - Marine data from Countryside Council for Wales (CCW) Technical Support (Research & Monitoring) Contracts, Wales. 12 records from MedOBIS (EurOBIS). 6 records from Colecciones Zoológicas de la Universidad de León, Colección de Malacostráceos. 1 records from Marine Conservation Society - Seasearch Marine Surveys . 21 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 1 records from MarBEF Publication Series data (EurOBIS). 1 records from Marine Invertebrata specimen database of Osaka Museum of Natutal History. 3 records from Porcupine Marine Natural History Society - Marine flora and fauna records from the North-east Atlantic. 2 records from (Table B) Fauna associated with Bathymodiolus azoricus mussel beds within the Lucky Strike hydrothermal field, Mid-Atlantic Ridge. 2 records from Museum Victoria provider for OZCAM. 2 records from Collection Crustacea SMF. 115 records from EPA'S EMAP Database. 11 records from Taxonomic Information Sytem for the Belgian coastal area (EurOBIS). 2 records from Crustacea specimens of Kuroshio Biological Research Foundation. 11 records from Sponges of Rathlin Island. 3 records from Arctic soft-sediment macrobenthos (EurOBIS). 13 records from Invertebrate Zoology Division, Yale Peabody Museum. 3 records from (Table C) Fauna associated with Bathymodiolus azoricus mussel beds within the Rainbow hydrothermal field, Mid-Atlantic Ridge. 89 records from NMNH occurrence DwC-A. 44 records from Australian Museum provider for OZCAM. 2 records from Queensland Museum provider for OZCAM. 5 records from South Western Pacific Regional OBIS Data All Sea Bio Subset (South Western P acific OBIS). 7 records from Colección Nacional de Invertebrados - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 57 records from Centre for Environmental Data and Recording - Marine Data from Northern Ireland. 3 records from Scottish Natural Heritage - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by Scottish Natural Heritage. 37 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 16 records from RBINS collections. 3 records from Museum of Comparative Zoology, Harvard University. 7 records from Diversidad bentónica de la laguna Celestún, Yucatán.
Keywords: GBIF; biodiversity; species occurrences